Feline Immunodeficiency Virus-Infected Cat Sera Associated with the Development of Broad Neutralization Resistance In Vivo Drive Similar Reversions In Vitro - Giannecchini, Simone (American Society for Microbiology, 2001)
We previously reported that, upon reinoculation into cats, a neutralization-sensitive, tissue culture-adapted strain of feline immunodeficiency virus constantly reverted to the broad neutralization resistance typical of primary virus isolates and identified residue 481 in the V4 region of the surface glycoprotein as a key determinant of the reversion. Here, we found that well-characterized immune sera, obtained from cats in which such reversion had occurred, selected in tissue culture in favor of virus variants that also had a neutralization-resistant phenotype and had amino acid 481 changed, thus indicating that the host's humoral immune response is capable of driving the reversion in the absence of other intervening factors. In contrast, a second group of immune sera, elicited by a virus variant that had already reverted to neutralization resistance in independent cats, induced the emergence of escape mutants lacking broad neutralization resistance and neutralized fewer virus variants. It is proposed that the viral variants used to produce the two sets of sera may have generated different antibody repertoires.